Gereja dan Kemiskinan: Respons Sosial Gereja Katolik Santo Barnabas Pamulang Timur terhadap Kemiskinan Perkotaan - Marhadi Marhadi; Moh. Nuh HS (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This article examines the relationship between the Church and poverty by analyzing the social response of the Santo Barnabas Catholic Church in Pamulang Timur to urban poverty. Poverty is understood not merely as economic deprivation, but as a social phenomenon shaped by structural inequality, limited access to education, health, and economic resources, as well as unequal social relations in urban settings. This study employs a qualitative case study approach. Data were collected through in-depth interviews with parish priests, members of the Social and Economic Development Section, social ministry volunteers, and observations of church-based social programs. The findings reveal that the Santo Barnabas Catholic Church addresses urban poverty not only through charitable assistance, but also through sustainable empowerment programs in education, health, and community economic development. This social response is carried out through organized and institutionalized church engagement aimed at strengthening social solidarity at the community level. These practices reflect the Church’s role as a social actor implementing reflective and contextual faith-based activism grounded in Catholic Social Teaching. The article highlights the significant contribution of the Church in responding to urban poverty and fostering social solidarity within a plural urban society.